2015
DOI: 10.1111/tpj.12838
|View full text |Cite
|
Sign up to set email alerts
|

Gene targeting by the TAL effector PthXo2 reveals cryptic resistance gene for bacterial blight of rice

Abstract: SUMMARYBacterial blight of rice is caused by the c-proteobacterium Xanthomonas oryzae pv. oryzae, which utilizes a group of type III TAL (transcription activator-like) effectors to induce host gene expression and condition host susceptibility. Five SWEET genes are functionally redundant to support bacterial disease, but only two were experimentally proven targets of natural TAL effectors. Here, we report the identification of the sucrose transporter gene OsSWEET13 as the disease-susceptibility gene for PthXo2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
272
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 449 publications
(280 citation statements)
references
References 29 publications
5
272
0
3
Order By: Relevance
“…With regard to on-target gene disruption via NHEJ, the potential environmental implications also require scrutiny, in particular if the gene disruption confers herbicide or disease resistance (Butler, et al 2015;Li, et al 2012;Wang, et al 2014;Zhou, et al 2015).…”
Section: Risk-benefit Communicationmentioning
confidence: 99%
“…With regard to on-target gene disruption via NHEJ, the potential environmental implications also require scrutiny, in particular if the gene disruption confers herbicide or disease resistance (Butler, et al 2015;Li, et al 2012;Wang, et al 2014;Zhou, et al 2015).…”
Section: Risk-benefit Communicationmentioning
confidence: 99%
“…Rice is the most frequently used crop species for testing and applying CRISPR‐Cas9 tools. Several agronomic traits of rice, including yield, fertility, architecture, biotic and abiotic stress response, and herbicide tolerance, have been successfully modified by targeted mutations in one or multiple major genes (Ikeda et al ., 2016; Li et al ., 2016a,b,c; Osakabe et al ., 2016; Sun et al ., 2016; Wang et al ., 2016; Xu et al ., 2014, 2016; Zhou et al ., 2015). …”
Section: Introductionmentioning
confidence: 99%
“…oryzae indicates that this pathogen enhances the release of sucrose from the host cells by inducing expression of OsSWEET13, a member of Clade III. Targeted mutation of OsSWEET13 led to reduced pathogenesis (Zhou et al, 2015). Earlier it was shown that two other Clade III SWEETs (OsSWEET11 and OsSWEET14) were also targets of bacterial rice blight (Li et al, 2013;Streubel et al, 2013).…”
Section: Introductionmentioning
confidence: 99%